A study to evaluate ocular changes in patients undergoing spine surgery in the prone position - Kiranpreet Kaur; Neetu Khanduri; Sumit Sachdeva; Roop Singh; Mamta Bhardwaj; Manju Bala (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: A present prospective study was conducted to evaluate ocular changes occurring in patients undergoing spine surgery in the prone position. Material and Methods: A total of 44 patients of either sex, belonging to American society of Anaesthesiology I and II (aged 18-60 years) scheduled for elective spine surgery in prone position were enrolled in the study. Baseline IOP and MAP measurement were taken prior to induction. After induction of anaesthesia patients were intubated using flexo-metallic tube of appropriate size. IOP and MAP were recorded after induction of anaesthesia, following completion of surgery and immediately after turning the patient supine and 30 min following extubation. Blood loss and duration of surgery was also noted. The OPP was derived using the formula (OPP = MAP-IOP). Ophthalmic examination was also performed using direct and indirect ophthalmoscopy on the day prior to surgery and on first post-operative day to rule out anterior ischemic optic neuropathy (AION), posterior ischemic optic neuropathy (PION), and retinal ischemia. Results: Mean IOP significantly increased (18.91 ± 3.56 mm Hg) (P < 0.001) at the end of surgery as compared to baseline value 12.85 ± 3.07 mm Hg. As a result mean OPP significantly reduced (75.12 ± 16.45) (P = 0.0018) at the end of the procedure. Conclusion: In patient's undergoing spine surgery in the prone position, careful patient positioning with no extrinsic pressure on the eyes, minimal surgical time and blood loss, and prevention of intraoperative hypotension, should be ensured to prevent the IOP rise and a reduction in OPP which can further prevent post-operative visual disturbance.